Multi-skeletal PtPdNi nanodendrites as efficient electrocatalyst with high activity and durability towards oxygen reduction reaction. (12th July 2022) - Li, Weicong; Bhuvanendran, Narayanamoorthy; Zhang, Weiqi; Xu, Qian; Hooshyari, Khadijeh; Su, Huaneng
Abstract: Engineering alloy nanostructures with a combination of highly active noble metals (Pt and Pd) and less electronegative non-noble metal (Ni) is found to be crucial for improving surface reactivity by enriching with active Pt sites. Herein, a multi-skeletal PtPdNi nanodendrites (NDs) was successfully formed by a simple one-pot method with structure directing agent. The modification of Pt electronic structure and their interaction due to compressive strain were explored using benchmark characterization techniques, which showed that the PtPdNi NDs possess Pt-enriched surface, corroborating to more active catalyst sites for oxygen reduction reaction (ORR) in acidic medium. The PtPdNi NDs have a higher electrochemical surface area (63 m 2  g −1 ) and an earlier onset potential (1.01 V) than PtPd NDs, PtNi NDs, and commercial Pt/C catalysts, indicating the outstanding ORR performance. The high mass and specific activities, as well as superior durability after accelerated degradation test (ADT), highlight the remarkable electrocatalytic performance of PtPdNi NDs over others. As a result, enhancing Pt utilization through the formation of PtPdNi NDs could be a reliable strategy to improve ORR electrocatalysis for polymer electrolyte membrane fuel cell (PEMFC) applications. Highlights: A PtPdNi nanodendrites (NDs) catalyst was prepared by a facile one-pot method. The presence of Ni facilitates the formation of uniform dendrite morphology. The PtPdNi NDs possess multi-skeletal structure and Pt-enriched surface. The PtPdNi NDs demonstrated superior activity and durability towards ORR.